A new variable structure controller for robot manipulators - Tenreiro Machado, J. A. (1988)
A new variable structure control algorithm for robot manipulators is announced. Second order linear system sliding curves and a new control law, eliminate the reaching phase problems as well as the chattering usually present in the sliding mode. The results show a remarkable improvement over conventional VSS controllers, maintaining, however, a low computationla complexity which make it well suited for microcomputer implementation. Furthermore, the well known standard heuristic procedures of controller adjustment can be used in the proposed scheme. This is of utmost importance in an industrial environment.